Pre-existing serum indoxyl sulfate and COVID-19 outcomes in patients undergoing hemodialysis: A retrospective cohort study - Stepanova, N.; Driianska, V.; Korol, L.; Snisar, L.; Savchenko, S. (Ukrainian Journal of Nephrology and Dialysis, 2023)
Patients undergoing hemodialysis (HD) are at increased risk of severe complications from COVID-19 due to compromised immune function and comorbidities. This retrospective study aimed to investigate the association between pre-existing serum indoxyl sulfate (IS) concentrations and COVID-19 outcomes in HD patients. Methods. Data on pre-existing IS and proinflammatory cytokines, such as interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), and tumor necrosis factor-alpha (TNF-α) were extracted from an existing patient database. The patients were followed up for 1.5 years and compared according to median serum IS concentration: low-IS (< 22.2 μg/mL) and high-IS (≥22.2 μg/mL) groups. The primary outcomes focused on assessing the risk and severity of COVID-19 infection. Results. A total of 56 patients aged 62 (56-67) years with a dialysis vintage of 37.5 (30-168) months were included in the analysis. Serum levels of IS were significantly correlated with Kt/V values (p = 0.043), arterial hypertension (p = 0.001), IL-6 (p = 0.023), MCP-1 (p = 0.023), and TNF-α (p = 0.033) concentrations. Elevated serum IS levels were significantly associated with an increased risk of COVID-19 infection (p < 0.0001) and a higher likelihood of hospitalization (p = 0.03). Patients with higher IS levels exhibited more severe lung involvement (p < 0.0001) and a greater need for respiratory support (p = 0.004). A serum IS concentration of 21.5 μg/mL was the optimal threshold for predicting COVID-19 infection in HD patients (sensitivity of 83.4% and specificity of 92.3%, p < 0.0001). Conclusion: Our study highlights the detrimental impact of serum IS on COVID-19 infection and its clinical outcomes in patients undergoing HD. Further research is warranted to elucidate the underlying mechanisms and explore potential therapeutic strategies targeting IS in this population.